Price Formation of Exhaustible Resources: An Experimental Investigation of the Hotelling Rule - Christoph Neumann; Mathias Erlei (Technische Universität Clausthal, Abteilung für Volkswirtschaftslehre, 2014)
In 1931 Harold Hotelling published his seminal contribution to the economic theory of exhaustible resources. His major insight states that the prices of exhaustible resources - more specifically the scarcity rent - will rise at the rate of interest, and consumption will decline over time. The equilibrium implies social optimality. However, empirical analysis shows that market prices of exhaustible resources rarely follow the predicted pattern. Yet our experimental investigation provides support for the position that the Hotelling rule is relevant for the long term development of resource prices.
Keywords: 330; Exhaustible resource; Hotelling rule; Intertemporal Allocation Problem; Continuous Double Auction; Experiment